Pulmonary function tests and their associated factors in people living with HIV at Jimma medical center; Ethiopia: a comparative cross-sectional study - Azezew, Muluken Teshome; Gobena, Teshome; Mengstie, Misganaw Asmamaw; Mulat, Elias (Frontiers in Reproductive Health, 2023)
Background People living with HIV (PLHIV) have a greater risk of developing respiratory disorders. The problems are linked to poor socio-economic status, high viral load, low CD4 counts, and antiretroviral therapy. Despite the high prevalence of respiratory disorders, the association between HIV infection and pulmonary function status, as well as the associated factors, is not well established in resource-limited countries. Methods A comparative cross-sectional study was conducted from September 24 to October 15 2020 at Jimma Medical Center among people living with HIV who were arranged into an age–sex-matched comparison group. Data were collected using a pretested structured questionnaire administered via face-to-face interviews. The collected data included socio-demographic, respiratory, HIV infection, and substance use variables. Pulmonary function tests were conducted using an SP10 spirometer. The collected data were entered and analyzed using SPSS version 26. Independent t-test and multiple linear regressions were carried out to identify factors associated with the pulmonary function status of the study participants. Results A total of 96 PLHIV and 96 matched control individuals participated in the study. The mean of pulmonary function test parameters among the PLHIV respondents was FVC (l) (67.35 ± 19.12, p0.003), FEV1s (l) (61.76 ± 16.04, p0.001), and PEFR (50.14 ± 23.32, p0.001), with a significant lowering in the study group. Female sex, respiratory symptoms, duration of HIV, duration of treatment, and khat chewing were associated with lowered FEV1s (l) (p < 0.05) in HIV-positive respondents. Conclusion PLHIV had significantly lower mean lung function parameters than HIV-uninfected participants. As a result, health providers should screen HIV-positive patients with respiratory symptoms, prolonged duration of HIV infection, prolonged treatment, and khat chewing for non-infectious lung disorders while treating them.